FRI0402 Disease Flare Patterns and Predictors in a Long-Term Follow-Up of 423 Japanese SLE Patients from Monocentric Cohort Jude Study. (9th June 2015) - Amano, H.; Ando, S.; Minowa, K.; Watanabe, T.; Ogasawara, M.; Morimoto, S.; Tokano, Y.; Yamaji, K.; Tamura, N.; Takasaki, Y.
Abstract : Background: Although the prognosis for systemic lupus erythematosus (SLE) has greatly improved, many patients experience the disease flare-up. Little is known about the disease flare-up patterns and predictors in a long-term follow up. Objectives: The aim of this study was to clarify the outcomes and predictors for disease flare-up in a monocentric cohort of Japanese patients with SLE. Methods: Among 2390 SLE patients registered in our JUDE (Juntendo University Database of Erythematosus) study, diagnosed between 1964 and 2004, 423 for whom long-term follow-up was possible between 1973 and 2012 were investigated. Disease activity patterns were defined using the SLE Disease Activity Index-2000 (SLEDAI-2K) 1 .Disease flare-up was defined according to the SELENA-SLEDAI flare composite 2 . SLE patients were included if they fulfilled the ARA 3 or ACR 4 criteria for SLE. Data on disease activity, severe flare-up and treatment were collected, and the initial clinical manifestations of disease flare-up were analyzed. The censoring period for analysis was May to October 2013. Results: The mean follow-up duration was 25.9 years. During follow-up, 118 (27.9%) of the 423 patients experienced at least once flare-up after initial treatment with corticosteroid or corticosteroid plus immunosuppressant. More than half (58.5%) of the patients who suffered flare-up were accumulated within 5 years, irrespective of the initial therapy. Comparison of the age at onset among patients who suffered flare-up more than twice in 10 years after the initial therapy showed that teenage onset accounted for a greater proportion than patients who developed SLE in their thirties and beyond. The most common manifestation associated with flare-up was thrombocytopenia. Cluster analysis showed that renal disturbance was distinct from arthritis among manifestations of both onset and flare-up. Conclusions: This long-term monocentric cohort follow-up study of 423 Japanese SLE patients revealed that 27.9% suffered flare-up after the initial therapy, irrespective of the initial treatment regimen. References: Gladman DD, Ibañez D, Urowitz MB. Systemic lupus erythematosus disease activity index 2000. J Rheumatol. 2002 29(2):288-91. Petri M, Kim MY, Kalunian KC, Grossman J, Hahn BH, Sammaritano LR, Lockshin M, Merrill JT, Belmont HM, Askanase AD, McCune WJ, Hearth-Holmes M, Dooley MA, Von Feldt J, Friedman A, Tan M, Davis J, Cronin M, Diamond B, Mackay M, Sigler L, Fillius M, Rupel A, Licciardi F, Buyon JP; OC-SELENA Trial. Combined oral contraceptives in women with systemic lupus erythematosus. N Engl J Med. 2005 15;353(24):2550-8. Tan EM, Cohen AS, Fries JF, Masi AT, McShane DJ, Rothfield NF, Schaller JG, Talal N, Winchester RJ. The 1982 revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum. 1982 25(11):1271-7. Hochberg MC. Updating the American College of Rheumatology revised criteria for the classification of systemic lupus erythematosus. Arthritis Rheum. 1997 40(9):1725 Disclosure of Interest: None declared